PEMIKIRAN RASIONAL PERAWATAN SALURAN AKAR - Winiarti Sidharta (Faculty of Dentistry, Universitas Indonesia, 2015)
The longevity of a tooth is based not on the pulp, but on the health of the attachment apparatus. Microorganism and their toxic products can passed out into the periapical tissue and generates lesions of endodontic origin. The rationale of root canal treatment now is based on biologic principles. Healing will occur if biomechanical preparation, cleaning and shaping were properly executed, and the root canal system is hermetically sealed in three dimension.